2021
DOI: 10.15294/komunitas.v13i1.27021
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks: The Survival Strategy Of Indonesian Migrant Workers In Hong Kong

Abstract: Transnational migration performed by Indonesian women today is a social transformation in labor participation. This phenomenon is also encountered in the lives of women who decide to become Indonesian migrant workers in Hong Kong. This research aims to analyze and identify the self-actualized survival ability of Indonesian migrant workers in Hong Kong. In addition, this research also investigates the social capital practiced by Indonesian migrant workers in Hong Kong. The descriptive qualitative method was emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…"… Like a Family": A Welcoming Community 230 Going Back While there are many elements at play, Blumenstock, Chi, and Tan (2019) argue that a solid social network is a major motivator for migrant workers to remain in their host country. Kiranantika (2021) lists that trust, social engagement, and reciprocity are the three pillars of survival strategies in countries that host migrant workers. Informants in this study were found to congregate in local groups and communities; these connections are important to informants as they offer a space where they are able to trust one another and lean on one another for emotional support while they are far from home and their families for work.…”
Section: Discussionmentioning
confidence: 99%
“…"… Like a Family": A Welcoming Community 230 Going Back While there are many elements at play, Blumenstock, Chi, and Tan (2019) argue that a solid social network is a major motivator for migrant workers to remain in their host country. Kiranantika (2021) lists that trust, social engagement, and reciprocity are the three pillars of survival strategies in countries that host migrant workers. Informants in this study were found to congregate in local groups and communities; these connections are important to informants as they offer a space where they are able to trust one another and lean on one another for emotional support while they are far from home and their families for work.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon can also be observed in the lives of women who choose to become migrant laborers. (Anggaunitakiranantika, 2021)…”
Section: Worker Rationality Theory In Migration Decision Makingmentioning
confidence: 99%
“…According to Buchdadi et al (2022), migrant workers in Taiwan are able to manage their household finances and are expected to enhance their family's welfare. Additionally, LCWs can enhance their self-actualization by diversifying their work (Anggaunitakiranantika, 2021). However, previous research has not thoroughly explored LCWs' survival strategies in achieving migration expectations.…”
Section: Introductionmentioning
confidence: 99%